SURVIVAL STRATEGIES FOR EVENT ORGANIZERS DURING A PANDEMIC FROM THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Muhammad Iqbal (Tasharruf: Journal Economics and Business of Islam, 2022)
This research was conducted to see how service business owners who focus on event organizers are surviving during a pandemic. by conducting this research, we hope that the strategies implemented by surviving entrepreneurs can be duplicated and applied to other companies. Data collection techniques in this study used observation, interview, and documentation techniques. The result of this research at PT. Orbit Semesta Production implements several strategies, including action, investment, and operations. The company has also fulfilled the elements of business according to the Islamic view by not doing things that are not in line with PT. Turindo also carries out a business divestment strategy by streamlining operational offices and transferring resource functions through online media. In applying business ethics, business people follow the elements of ethics. In other businesses, CV. Flazh Production implements a reduction strategy, namely cutting team member rights, because the new production strategy does not follow what has been implemented in entrepreneurial ethics, such as not helping and being responsible for what the company owns.